Utilization of The Mobile Application of National Health Insurance (JKN) To Increase The Effectiveness of Services BPJS Insurance In Sibolga - Benri Situmorang (Science Midwifery, 2022)
Currently, the government has developed several mobile applications for the National Health Insurance (JKN) to facilitate services for patients. The development of some of these applications aims to help consumers and support patient-centered decisions in choosing which benefits to choose (Bundorf et al., 2019). The digital transformation of the Badan Penyelenggara Jaminan Sosial (BPJS) is to provide convenience for BPJS users or the public, such as paying BPJS contributions, changing membership data, knowing family participant data, etc (Kipo-Sunyehzi, 2021). The aims of this study is to determine the use of the national health insurance application (JKN) to increase the effectiveness of BPJS health services in the city of Sibolga. The type of research taken is descriptive research with a qualitative approach. This study took as many as four resource persons. While the data collection technique is using the technique of observation, interviews and documentation. The results showed that through the national health insurance (JKN) mobile application, all administrative services at the Sibolga City BPJS office for patients became more effective and efficient. This shows that the benefits of the JKN mobile application have proven to be very helpful in accessing BPJS health services.